Replacing the Words "Palestinian Support" with "Criminal Justice for Palestine", Which Shifts the Meaning from Mere Diplomatic Political Support to Demands for Substantial Criminal Law Enforcement : Penelitian - Ely Sukmana (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
International support for the Palestinian struggle for independence has for decades been dominated by diplomatic-political rhetoric and non-binding resolutions that have failed to halt impunity and violations of international law. This study aims to examine the paradigmatic shift in global support from mere formal diplomatic alignment to demands for substantial criminal law enforcement through criminal justice mechanisms. Using normative legal research methods with conceptual, statutory, and comparative approaches, this article analyzes the urgency of activating the jurisdiction of the International Criminal Court (ICC) and the application of universal jurisdiction by third countries to prosecute war crimes, crimes against humanity, and genocide in the Palestinian territories. The study's findings indicate that conventional diplomatic approaches have reached saturation point due to the geopolitical veto power of the UN Security Council. Conversely, articulating support in the form of substantive criminal law enforcement offers an objective path to legal accountability, shifting Palestine's status from an object of political negotiation to a legal subject entitled to retributive justice and genuine reparation.